The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/educsci11020075
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Astronomy. Development of the Shape of the Earth Concept in Polish Children between 5 and 10 Years of Age

Abstract: The Earth’s shape concept develops as consecutive cognitive problems (e.g., the location of people and trees on the spherical Earth) are gradually resolved. Establishing the order of problem solving may be important for the organisation of teaching situations. This study attempted to determine the sequence of problems to be resolved based on tasks included in the EARTH2 test. The study covered a group of 444 children between 5 and 10 years of age. It captured the order in which children solve cognitive problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…In addition, the drama activities stated by Akerblom et al [32] that were employed to teach the state of water and its molecular nature to pupils aged 6 years old. Finally, the dramatic activities about thermal insulation pointed out by Fragkiadaki et al [33] and Jelinek [34] that clearly highlighted the contribution of the social, cultural, and material environment in the development of the scientific thinking of children.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the drama activities stated by Akerblom et al [32] that were employed to teach the state of water and its molecular nature to pupils aged 6 years old. Finally, the dramatic activities about thermal insulation pointed out by Fragkiadaki et al [33] and Jelinek [34] that clearly highlighted the contribution of the social, cultural, and material environment in the development of the scientific thinking of children.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, there is a tendency to conduct research examining the processes of concept formation about climate change, and empirical research focussing on an understanding of how such concepts can be translated into action is still required. Here, parallels between empirical research exploring how young children develop a variety of scientific concepts ranging from astronomy [51], sound [52,53], and light [54], to heat transfer [55] can be used to transfer the findings to the current inquiry. Some of these studies [51][52][53][54][55] have also explored educational frameworks that promote scientific literacy in young children and some have examined the critical role of the teacher, the importance of child-teacher interactions and communication during science learning [56,57], and the importance of parental involvement in science learning in the early years [58].…”
Section: Discussionmentioning
confidence: 99%
“…Here, parallels between empirical research exploring how young children develop a variety of scientific concepts ranging from astronomy [51], sound [52,53], and light [54], to heat transfer [55] can be used to transfer the findings to the current inquiry. Some of these studies [51][52][53][54][55] have also explored educational frameworks that promote scientific literacy in young children and some have examined the critical role of the teacher, the importance of child-teacher interactions and communication during science learning [56,57], and the importance of parental involvement in science learning in the early years [58]. Together, these studies indicate that multiple and complex understandings of scientific and technical concepts are formed early in life via children's everyday experiences and interactions with others around them.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly interesting because, based on individual research aims found in relevant studies, it is possible to ascertain whether, and under which circumstances, it is possible to achieve cognitive transformation. For example, the main characteristics of a developmental course were found in research studying the development of 5-10 year-old children's mental representations regarding the shape of the Earth; truly, children were found to initially construct in their thought the idea of a spherical Earth, and then proceed to conceive of the relationship between the Earth and the sun [26]. Furthermore, "the order of resolving cognitive problems was established.…”
Section: The Mental Representationsmentioning
confidence: 99%
“…It was found that children first solve the problem of how people move on Earth, then their location, as well as the location of clouds, the Sun at night and trees. Finally, children match the way a kicked ball moves on Earth and the phenomenon of nightfall" [26].…”
Section: The Mental Representationsmentioning
confidence: 99%